NEW DIRECTIONS IN LANGUAGE LEARNING: COMBINATION OF ONLINE RESOURCES AND BLENDED LEARNING (Scientific journal of the Fergana State University, 2024)
In this article it is dedicated to the study of the development of online resources that define new trends in language learning. The article provides a comprehensive analysis of online tools, gamification elements, and blended learning models that have emerged in the dynamic field of language teaching. The interactive, personal, and often ever-changing nature of language learning platforms is also addressed.